Microneedling: An Innovative Technique for Gingival Depigmentation - Chetna Bhambhu; Vidushi Sheokand; Shikha Sharma; Amit Bhardwaj (Indian Journal of Dental Sciences)
Microneedling is a form of therapy that creates a controlled skin injury using a device consist rows of microneedles that puncture a uniform depth into the dermis creating micropuncture that heals quickly, stimulating the formation of collagen and elastin fibers and ultimately leads to remodeling of the skin. It was originally introduced for skin rejuvenation including acne scars, acne, posttraumatic/burn scars, hyperhidrosis, and stretch marks. In a brief period, this technique has become popular and widely accepted because it is an easy, cheap, efficient method that requires very little training. Conventionally, collagen induction has been used in the treatment of facial scars and skin rejuvenation, but it is being switched to dental procedures as a new technique for depigmentation, target drug delivery devices, collection of diagnostic fluids, etc.